Earning Management Dalam Penawaran Saham Perdana Pada Tahun 2008 - 2010 Di Bursa Efek Indonesia - Nasir, Azwir; Basri, Yesi Mutia; Nurmalasari, Yutri (Jurnal Ekonomi, 2012)
This research to test whether earnings management occurred when the company go public in Indonesia Stock Exchange. This study is a replication of the Irawan and Gumanti (2008) to see the significance before going public with the public and at the current moment to go public after going public. It is also intended to test the results of previous studies in different contexts. This study used a sample of firms that went public between 2008 to 2010. This study used 32 companies that conduct its first stock offering (Initial Public Offering or IPO) on the Indonesia Stock Exchange selected using purposive sampling method. In this study, researchers used an instrument marked Wilcoxon rank test using SPSS version 19.0. Research results indicate that there is no earnings management exhibited significance between earnings management before going public with go public now, and after a while go public with go public.